Physical activity and health status of the elderly - Ćwirlej-Sozańska, Agnieszka (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Demographic changes represented by the aging of the Polish population lead to increasing costs related to e.g. health care and social benefits and result in the necessity to introduce systematic solutions for maintaining and improving health and fitness in senior citizens.The purpose of the study was to assess the impact of physical exercise on the maintenance of higher performance parameters by the elderly. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: 220 individuals were examined, and further analysis was based on complete results acquired from 198 persons aged 60–70, including 102 females and 96 males. All the subjects were able to independently handle all routine activities. Based on the assessment of their physical activity, the subjects were divided into the study group (65 individuals – 32 females and 33 males), which included individuals on average involved in physical activities for the minimum of 75 min/week (walks, cycling, exercise, etc.) and the control group consisting of those with no or low level of motor activity (133 individuals – 70 females and 63 males). The study investigated the relation between physical activity and health, sense of well-being, assessment of quality of life and level of vitality. The study employed standardized questionnaire designed by this author. Statistical analysis was conducted using chi-square test of independence and Student’s t-test. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The findings show a statistically significant correlation between the higher level of motor activity in the elderly and better assessment of their health, well-being, quality of life and level of vitality. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: It is necessary to initiate systematic measures aimed at promoting active life-style, and in particular physical exercise, among present and future senior citizens, by implementing preventive measures supporting the process of aging successfully